Serpulanines A to C, N‐Oxidized Tyrosine Derivatives Isolated from the Sri Lankan Fungus Serpula sp.: Structure Elucidation, Synthesis, and Histone Deacetylase Inhibition - Williams, David E.; Gunasekara, Niranjan W.; Ratnaweera, Pamoda B.; Zheng, Zehua; Ellis, Samantha; Dada, Sarah; Patrick, Brian O.; Wijesundera, Ravi L. C.; Nanayakkara, C.M.; Jefferies, Wilfred A.; de Silva, E. Dilip; Andersen, Raymond J. (My University, 2018)
Serpulanines A (1), B (2), and C (3) have been isolated from extracts of the rare Sri Lankan macrofungus Serpula sp. The structures of 1, 2, and 3 were elucidated by a combination of spectroscopic and single-crystal X-ray diffraction analyses. Serpulanines A (1) and B (2) both contain the rare (E)-2-hydroxyimino hydroxamic acid functional group array. A proposed biogenesis for serpulanine B (2) suggests that its (E)-2-hydroxyimino hydroxamic acid moiety arises from a diketopiperazine precursor. Synthetic serpulanine A (1) inhibited class I/II histone deacetylases in murine metastatic lung carcinoma cells with an IC50 of 7 μM.